2021
DOI: 10.1016/s2665-9913(21)00070-9
|View full text |Cite
|
Sign up to set email alerts
|

Mavrilimumab in patients with severe COVID-19 pneumonia and systemic hyperinflammation (MASH-COVID): an investigator initiated, multicentre, double-blind, randomised, placebo-controlled trial

Abstract: Background In patients with COVID-19, granulocyte-macrophage colony stimulating factor (GM-CSF) might be a mediator of the hyperactive inflammatory response associated with respiratory failure and death. We aimed to evaluate whether mavrilimumab, a monoclonal antibody to the GM-CSF receptor, would improve outcomes in patients with COVID-19 pneumonia and systemic hyperinflammation. Methods This investigator-initiated, multicentre, double-blind, randomised trial was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 27 publications
0
57
0
5
Order By: Relevance
“…Mavrilimumab, a monoclonal antibody that acts as a GM-CSF alpha-receptor antagonist demonstrated non-significant trends of 48% improvement in survival without requirement for supplemental oxygen. 27 Otilimab, a monoclonal antibody targeting circulating GM-CSF in ventilated subjects, was reported in a non-peer-reviewed disclosure of results from its phase 2b COVID-19 study (NCT04376684) to not meet its primary endpoint of improvement in the proportion of COVID-19 subjects who were alive and free of respiratory failure 28 days; however, in pre-planned analysis of subjects aged at least 70 years, which comprised 22% of the entire patient population, 65.1% were alive and free of respiratory failure, compared to 45.9% of subjects who received the standard of care. 28 The results of all three trials of GM-CSF antagonism suggest the central role of GM-CSF in CS of COVID-19 that has been recently demonstrated through network analysis of cytokine profiles from COVID-19 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Mavrilimumab, a monoclonal antibody that acts as a GM-CSF alpha-receptor antagonist demonstrated non-significant trends of 48% improvement in survival without requirement for supplemental oxygen. 27 Otilimab, a monoclonal antibody targeting circulating GM-CSF in ventilated subjects, was reported in a non-peer-reviewed disclosure of results from its phase 2b COVID-19 study (NCT04376684) to not meet its primary endpoint of improvement in the proportion of COVID-19 subjects who were alive and free of respiratory failure 28 days; however, in pre-planned analysis of subjects aged at least 70 years, which comprised 22% of the entire patient population, 65.1% were alive and free of respiratory failure, compared to 45.9% of subjects who received the standard of care. 28 The results of all three trials of GM-CSF antagonism suggest the central role of GM-CSF in CS of COVID-19 that has been recently demonstrated through network analysis of cytokine profiles from COVID-19 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, given the known role of GM-CSF in emergency myelopoiesis and CAR-T cell associated cytokine release syndrome 75 , and the observation of increased numbers of GM-CSF producing T cells 31 and higher serum concentrations 45 of GM-CSF in some patients with COVID-19, blockade of systemic GM-CSF or its receptor was also proposed as a strategy to dampen hyperinflammation in severe COVID-19. At least six randomized clinical trials have been launched since the beginning of the pandemic 46 , one of which already reported promising results on a preprint server 76 , while another did not show benefit and was prematurely halted 77 . Major differences in outcome of GM-CSF interventions might depend on timing of intervention, but also on the route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…A possibility of Granulocyte-macrophage colony stimulating factor (GM-CSF) being a hyperinflammatory mediator was also questioned and thus Mavrilimumab, a monoclonal antibody to GM-CSF receptor came into the moonlight for testing the proposed hypothesis. 72 In a prospective cohort study by Giacomo De Luca et al, treatment with Mavrilimumab single intravenous dose (6 mg/kg) showed significant clinical outcomes. Further studies will have to be conducted to confirm the findings and prove the efficacy of this drug.…”
Section: Mavrilimumabmentioning
confidence: 98%